2021
DOI: 10.5194/bg-18-1105-2021
|View full text |Cite
|
Sign up to set email alerts
|

Key drivers of pyrogenic carbon redistribution during a simulated rainfall event

Abstract: Abstract. Pyrogenic carbon (PyC) is produced by the incomplete combustion of vegetation during wildfires and is a major and persistent pool of the global carbon (C) cycle. However, its redistribution in the landscape after fires remains largely unknown. Therefore, we conducted rainfall simulation experiments on 0.25 m2 plots with two distinct Swiss forest soils (Cambisol (clay loam) and Luvisol (sandy silt)). We applied PyC produced from wood (Picea abies) labeled under FACE conditions and C4 grass (Miscanthus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 100 publications
1
20
0
Order By: Relevance
“… 3 In fire-affected landscapes, fresh as well as aged PyC, in both dissolved and particulate forms, is mobilized to fluvial ecosystems via water erosion. 4 6 Indeed, the significant presence of charcoal in river bed deposits in fire-affected ecosystems was the subject of investigation decades ago 7 and hydrological events (e.g., stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time. 6 , 8 Coppola and colleagues 9 found that globally 15.8 ± 0.9% of riverine particulate organic carbon is of pyrogenic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 In fire-affected landscapes, fresh as well as aged PyC, in both dissolved and particulate forms, is mobilized to fluvial ecosystems via water erosion. 4 6 Indeed, the significant presence of charcoal in river bed deposits in fire-affected ecosystems was the subject of investigation decades ago 7 and hydrological events (e.g., stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time. 6 , 8 Coppola and colleagues 9 found that globally 15.8 ± 0.9% of riverine particulate organic carbon is of pyrogenic origin.…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 Indeed, the significant presence of charcoal in river bed deposits in fire-affected ecosystems was the subject of investigation decades ago 7 and hydrological events (e.g., stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time. 6 , 8 Coppola and colleagues 9 found that globally 15.8 ± 0.9% of riverine particulate organic carbon is of pyrogenic origin. Jones and colleagues 10 estimated that PyC accounts for 12 ± 5% of the riverine dissolved organic carbon (DOC, i.e., filtered <0.45 μm).…”
Section: Introductionmentioning
confidence: 99%
“…3 In fire-affected landscapes fresh as well as aged PyC, in both dissolved and particulate forms, is mobilized to fluvial ecosystems via water erosion. [4][5][6] Indeed, significant charcoal presence in river bed deposits in fire affected ecosystems have been the subject of investigation decades ago 7 and hydrological events (e.g. stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time. 6,8 Coppola and colleagues 9 found that globally 15.8 ± 0.9% of riverine particulate organic carbon is of pyrogenic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation